Implementation of Deep Breathing Relaxation and Early Mobilization to Overcome Pain and Mobility Problems in Post-Section Caesarean Mothers Indicated with Premature Rupture of Membranes in Patient, Mrs. R P3a0 at Rskb Columbia Asia - Sulistya Ningsih; Witri Hastuti (Sean Institute, 2026)
Sectio Caesarea is a surgical procedure performed to deliver a baby through an incision in the abdominal wall and uterus. This procedure may cause several NERS ing problems in the mother, such as acute pain, limited physical activity, and breastfeeding difficulties. In addition, infants born through surgical delivery may experience early adaptation problems, including the risk of ineffective thermoregulation, risk of infection, and risk of impaired attachment processes. Therefore, comprehensive NERS ing care is required to support maternal recovery and assist newborn adaptation. The purpose of this case study is to describe the implementation of NERS ing care for a post–Sectio Caesarea mother and her newborn using the NERS ing process approach, which includes assessment, NERS ing diagnosis, intervention planning, implementation, and evaluation. The method used in this study is a case study conducted on Mrs. M with post–Sectio Caesarea at the inpatient ward. The assessment results showed several NERS ing problems in the mother, including acute pain related to the surgical procedure, activity intolerance related to postoperative physical weakness, and ineffective breastfeeding related to breast engorgement and lack of optimal breastfeeding stimulation. In the newborn, the identified NERS ing problems included the risk of ineffective thermoregulation, risk of infection related to immature immune defense and umbilical cord care, and risk of impaired attachment process due to mother–baby separation. NERS ing interventions implemented included pain management, gradual mobilization, breastfeeding education, monitoring the baby's body temperature, umbilical cord care, and facilitating mother–infant bonding. After two days of NERS ing care, the condition of both mother and baby showed improvement, indicated by decreased pain levels, improved maternal activity tolerance, the initiation of breast milk production, stable neonatal temperature, and the beginning of mother–infant interaction. In conclusion, the implementation of a comprehensive NERS ing process can improve recovery in post–Sectio Caesarea mothers and support the physiological and psychological adaptation of newborns.